Insights from Small-N Studies - Gouvea, Julia (CBE Life Sci Educ, 2017)
Small-N studies have been relatively uncommon in biology education research and are likely less familiar to instructors and administrators than large-N studies. This group of recent papers illustrates how small-N studies can make contributions to education research and practice.